Understanding prejudice of psychic suffering individuals about sexuality - Gisela Cardoso Ziliotto; João Fernando Marcolan
ABSTRACT Objectives: to understand the conceptions of individuals in psychological distress about their sexuality. Methods: qualitative study held at a Psychosocial Care Center. Fifteen people assisted in the service participated. A semi-structured questionnaire and script with identification data survey and guiding questions were applied. Data were analyzed by Content Analysis. Results: the following categories emerged: Prejudice of assisted people regarding homosexuality; Prejudice of assisted people regarding the expression of sexuality and the social context; Prejudice to the affective relationship among people assisted in CAPS; Prejudice of people assisted in the expression of female sexuality; Prejudice of society to the sexual orientation of assisted people. Final considerations: sexuality understanding showed that these are conceptions linked to prejudice and stigma of society. Although sexuality was present, it is clear that it was surrounded by taboos, myths and value judgments, in which the only way to deal with it was through repression.